Death and a Dog (A Lacey Doyle Cozy Mystery-Book 2) - Fiona, Grace (Lukeman Literary, 2019)
DEATH AND A DOG (A LACEY DOYLE COZY MYSTERY-BOOK 2) is book two in a charming new cozy mystery series by Fiona Grace. Lacey Doyle, 39 years old and freshly divorced, has made a drastic change: she has walked away from the fast life of New York City and settled down in the quaint English seaside town of Wilfordshire. Spring is in the air. With last month's murder mystery behind her, a new best friend in her English shepherd, and a budding relationship with the chef across the street, it seems like everything's finally settling into place. Lacey is so excited for her first major auction, especially when a valuable, mystery artifact enters her catalogue. All seems to go without a hitch, until two mysterious bidders arrive from out of town-and one of them winds up dead. With the small village plunged into chaos, and with the reputation of her business at stake, can Lacey and her trusty dog partner solve the crime and restore her name? Book #3 in the series-CRIME IN THE CAFE-is also available for preorder!
Keywords: Krimi, detektivky